Identification of Potential Human Protein Targets for Soybean Isoflavones - Maldonado-Rojas,Wilson (2021)
Soy isoflavones have been reported as endocrine disruptors due to their ability to modulate the activity of estrogen receptors (ERs) in mammals; however, its ability to modulate other metabolic pathways is not entirely clear, which makes it necessary to identify new pharmacological targets that interact with these compounds present in soybean. In this work, a virtual screening was executed to identify potential targets of nine soy isoflavones, employing human proteins target from PharmMapper. The best 25 fit scores were selected and prepared for AutoDock Vina docking protocols. The results suggest that equol, daidzein and biochanin A, have the potential to interact with targets such as phenylethanolamine N-methyltransferase, sex hormone-binding globulin and vitamin D3 receptor, respectively. The validations of docking protocols showed good pose reproducibility (root-mean-square deviation (RMSD) ranged 0.001-3.854 Å) and a modest correlation between binding affinities and agonist concentration, AC50 (correlation coefficient (R) = 0.643, p < 0.001). Protein interaction network revealed that predicted targets for soy isoflavones are involved in different pathways, including neurotransmission, metabolism, and cancer remarking the need of a better understanding of the effects of these compounds on human health.